2014
DOI: 10.1111/tan.12477
|View full text |Cite
|
Sign up to set email alerts
|

Application of high‐throughput, high‐resolution and cost‐effective next generation sequencing‐based large‐scale HLA typing in donor registry

Abstract: Next generation sequencing (NGS)-based human leukocyte antigen (HLA) typing was used for ultra large-scale genotyping of registry donors for the China Marrow Donor Program (CMDP). More than 79,000 samples were subjected to HLA genotyping at 4-digit allelic level without ambiguities for HLA-A, -B, -C, DRB1 and DQB1 loci, with throughput up to 2068 samples per lane in a HiSeq flow cell (eight lanes per run), and cost reduced by 95% compared with that of Sanger-based typing. Two percent of randomly selected sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…In this two‐part review article, we described, analysed and discussed aspects of donor registry work related to immunogenetics and population genetics by using the example of DKMS. The major development at the intersection of immunogenetics and stem cell donor registries over the last few years has clearly been the use of NGS‐based high‐throughput HLA typing (Cereb, Kim, Ryu, & Yang, ; Lange et al, ; Schöfl et al, ; Zhou et al, ). We showed that this accomplishment had important immediate effects such as higher typing quality (higher resolution, less errors) and dramatic cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that patients with TM have a high rate of graft rejection due to the existence of HLA antibodies resulting from long‐term blood transfusion. The next generation sequencing HLA genotyping workshop played a potential role in selecting high compatibility of UDs in PBSCT . In our study, all patients received UD‐PBSCT with at most two allelic mismatches in addition to a high number of total nucleated cells/kg (9.6 × 10 8 /kg).…”
Section: Discussionmentioning
confidence: 99%
“…The next generation sequencing HLA genotyping workshop played a potential role in selecting high compatibility of UDs in PBSCT. 16,17 In our study, all patients received UD-PBSCT with at most two allelic mismatches in addition to a high number of total nucleated cells/kg (9.6 × 10 8 /kg).…”
Section: Discussionmentioning
confidence: 99%